Researcher Perspectives on Obstacles and Facilitators of Open Scholarship at a Canadian University - Rothfus, Melissa A.; MacLeod, Lachlan; Gillis, Louise; MacPherson, Erin (Partnership, 2024)
In 2022, researchers at Dalhousie University were surveyed to assess their understanding and practice of open scholarship. The survey was designed to answer these primary questions: what are Dalhousie University researchers' existing practices and levels of knowledge regarding open scholarship, and what is their awareness and perception of institutional support for open practices? Participants were recruited through direct email, blog posts, and newsletters from the Dalhousie Libraries, Faculty of Graduate Studies, Office of Research Services, and offices of the Associate Deans of Research.During the three-week period the survey was active,131 surveys were begun. As incomplete surveys were excluded from data analysis, the total analyzed sample size was 98. Descriptive analysis was conducted, as the number of responses was not representative of the Dalhousie University population.Most responses were from faculty, specifically in the Faculty of Medicine, followed by the Faculties of Science and Health. The majority of respondents reported sharing some type of scholarly output, though this varied by discipline and by material type. Informal sharing mechanisms were reported more frequently than formal repositories or publisher sites. Obstacles to open scholarship practices that were identified included concerns about investments of time, money, and education as well as concerns about institutional support and recognition. While many supports for open scholarship are available, there is a need to increase awareness.